Calcined stone self-compacting concrete as well as preparation method and application thereof
By using sintered stones as coarse aggregates, the contact area with the gelled material is increased, and the problems of high cost and low strength of self-condensed concrete are solved, and the effects of cost reduction and strength improvement are achieved.
Patent Information
- Application Number
- CN202510140640.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-29
AI Technical Summary
The existing self-finished concrete is costly to prepare, and due to the small contact area between natural gravel and gelling materials, the bonding performance is poor and the strength is low.
Sintered stones are used as coarse aggregates to increase their specific surface area by contacting them with the gelling material, thereby improving the bonding performance and compressive strength.
The preparation cost of self-finished concrete is reduced and its strength is increased by 20% compared to natural gravel.
Smart Images

Figure CN119899018A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of construction engineering and water conservancy engineering, and more specifically to a sintered stone self-compacting concrete and a preparation method and application thereof. Background Art
[0002] Self-compacting concrete refers to concrete that can flow and compact under its own gravity, completely fill the formwork even with dense steel bars, and has good homogeneity and does not require additional vibration. For example, during the construction process, if there are some structures that are difficult to vibrate at some nodes, self-compacting concrete can achieve good molding quality without vibration.
[0003] In the field of construction materials and water conservancy projects, self-compacting concrete has begun to be widely used in engineering projects. For example, hydraulic tunnels need lining construction to prevent tunnel collapse after excavation, which places high demands on the quality and strength of concrete. A good self-compacting concrete preparation method can improve construction efficiency. Because the preparation cost of self-compacting concrete is high, it will not be used on a large scale. Due to its high fluidity and no need for vibration, ordinary concrete cannot replace it.
[0004] The coarse aggregates in ordinary self-compacting concrete have different shapes, such as flake aggregates, needle-shaped aggregates, spherical aggregates, etc. The smooth surface has limited contact with the cementitious material produced by the cement hydration reaction, which affects the strength of the concrete. However, in the prior art, when preparing self-compacting concrete, sand and gravel with special particle grading are used as raw materials, and the preparation cost is relatively high, which limits its large-scale use. In addition, due to the small contact area between the natural crushed stone as coarse aggregate and the cementitious material during the preparation process, the bonding performance is poor and the strength is low.
[0005] How to reduce the preparation cost of self-compacting concrete so that it can be used on a large scale and how to improve the strength of self-compacting concrete has always been a research hotspot. Summary of the invention
[0006] In view of the above problems, the present invention provides a sintered stone self-compacting concrete and a preparation method and application thereof. When preparing the sintered stone self-compacting concrete, the present invention uses sintered stone as coarse aggregate, which not only reduces the preparation cost, but also the porous structure of the sintered stone is conducive to increasing the contact area with the cementitious material, thereby improving the bonding performance and compressive strength.
[0007] The first object of the present invention is to provide a sintered stone self-compacting concrete, which is made of the following components in parts by mass: 243 parts of cement, 233 parts of fly ash, 1055 parts to 1112 parts of sand, 515 parts to 623 parts of sintered stone, 204 parts to 210 parts of water, 6 parts to 8 parts of admixture, and 5 parts of sodium silicate.
[0008] More preferably, it is composed of the following components in parts by mass: 243 parts of cement, 233 parts of fly ash, 1069 parts of sand, 596 parts of sintered stone, 206 parts of water, 7 parts of admixture, and 5 parts of sodium silicate.
[0009] In a preferred embodiment of the present invention, the particle size of the sintered stone is 5 mm to 30 mm, and the bulk density is 800 kg / m 3 ~1200kg / m 3 .
[0010] In a preferred embodiment of the present invention, the admixtures are water reducing agent and air entraining agent, and the mass ratio of the water reducing agent to the air entraining agent is 10:1.
[0011] In a preferred embodiment of the present invention, the cement is ordinary Portland cement.
[0012] In a preferred embodiment of the present invention, the fly ash is grade I fly ash.
[0013] The second object of the present invention is to provide a method for preparing the above-mentioned sintered stone self-compacting concrete, comprising the following steps: After cement and fly ash are mixed evenly, sand and sintered stone are added and mixed evenly, and then admixtures, water and sodium silicate solution are added and mixed evenly and then cured to obtain sintered stone self-compacting concrete.
[0014] Specifically, when preparing sintered stone self-compacting concrete, cement and fly ash are added to a mixer and fully stirred to obtain powder material, sand and sintered stone are added to the powder material, and stirring is continued. The stirring process is to make the aggregate and powder material fully mixed and uniform, ensuring that there is no obvious unevenness. The addition of aggregate can make the powder material initially dispersed therein to form a relatively uniform mixture. After the stirring is completed, the admixture and water are slowly poured into the mixer in the working state, in order to make the molecules in the admixture evenly dispersed in the water, play its function of dispersing cement particles, and improve the fluidity of the concrete. Finally, sodium silicate solution is added and stirring is continued. During the stirring process, the sodium silicate solution can participate in the hydration reaction and react with the active substances in the fly ash to form cementitious substances such as silicate, and finally prepare sintered stone self-compacting concrete.
[0015] In a preferred embodiment of the present invention, the curing time is 28 days.
[0016] In a preferred embodiment of the present invention, the mass fraction of the sodium silicate solution is 15%.
[0017] The third object of the present invention is to provide the application of the above-mentioned sintered stone self-compacting concrete in dam engineering and lining engineering. In practical applications, the sintered stone self-compacting concrete prepared by the present invention can be used to enhance the flood resistance of Erdao Dam and assist in the regulation of water resources; at the same time, the sintered stone self-compacting concrete prepared by the present invention can adapt to complex underground engineering, reinforce surrounding rocks and provide long-term stable bearing capacity.
[0018] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a sintered stone self-compacting concrete, the raw materials used are cement, fly ash, sand, sintered stone, water, admixture and sodium silicate, sand is used as fine aggregate, sintered stone is obtained by burning coal, and is an object with a porous structure in slag, and the use of sintered stone can effectively reduce the preparation cost. The present invention uses sintered stone as coarse aggregate, because of the porous and irregular surface structure, the hydrated calcium silicate and other cementing substances produced by the cement hydration reaction are combined with the pores of the sintered stone, which not only increases the contact area, but also improves the strength of the self-compacting concrete. Compared with natural crushed stone, the strength of the self-compacting concrete mixed with sintered stone is increased by 20%. The active substances in the fly ash can react with sodium silicate to generate aluminosilicate cementing substances, which can promote the migration of ions and the progress of the reaction in water.
[0019] Sodium silicate reacts with silicon dioxide in fly ash: Na2O・nSiO2+SiO2=Na2O・(n+1)SiO2.
[0020] Sodium silicate reacts with alumina in fly ash: Na2O・nSiO2+Al2O3=Na2O・Al2O3・nSiO2.
[0021] (2) The admixture used in the present invention is composed of a water reducer and an air entraining agent, which are configured in a mass ratio of 10:1. Due to its efficient water reducing effect, it has a dispersing effect on the powder material, making the material mixing more uniform and enhancing the flow properties of the self-compacting concrete. Sintered stone as a lightweight aggregate can increase the viscosity of the concrete by adding a high-efficiency water reducer, so that the slurry can fully wrap the aggregate. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a physical picture of the sintered stone used in the present invention.
[0023] Figure 2 This is the effect of the amount of sintered stone added on the compressive strength. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The cement used in the present invention is Conch brand ordinary silicate cement P·O42.5, which includes 50% tricalcium silicate, 20% dicalcium silicate, 10% tricalcium aluminate and other silicate cement clinkers, other mixed materials and gypsum.
[0026] The fly ash used in the present invention generally has a 45 μm square mesh sieve residue of no more than 12% and a loss on ignition of no more than 5%, and belongs to Class I fly ash. Table 1 is a chemical composition table of the fly ash used in the present invention.
[0027] Table 1 Chemical composition of fly ash The sand used in the present invention is natural sand, and the sand has a mud content of 10% and a water content of 6%.
[0028] The sintered stone used in the present invention is a porous and glassy object in the slag, with a rough and porous surface, hard texture, irregular shape, continuous gradation of particle size between 5mm and 30mm, and a bulk density of 800kg / m 3 ~1200kg / m 3 Because sintered stone is the product of coal combustion, it has good thermal insulation performance.
[0029] The present invention adopts sintered stone as coarse aggregate. Due to its porous structure, the specific surface area is larger than that of natural crushed stone with the same particle size distribution, and the sintered stone is more closely connected with the cementitious material, thereby improving the compressive strength of the concrete.
[0030] The admixtures used in the present invention are a water reducer and an air entraining agent. The water reducer adopts a special water reducer produced by Beijing Huashi Nagu Technology Co., Ltd., model HSNG-T, and the air entraining agent adopts YQ-AE air entraining agent produced by Tianjin Xinyongqiang Admixture Company. The water reduction rates are 27.2% and 6.7% respectively. They are configured at a mass ratio of 10:1 to ensure the fluidity of the self-compacting concrete.
[0031] The present invention uses sintered stone as aggregate. Due to its porous structure, the cementitious material produced by the hydration reaction is more closely connected with it, while reducing the production cost; the active material in the fly ash reacts with sodium silicate to form main cementitious materials such as aluminosilicate.
[0032] Example 1 The present embodiment provides a sintered stone self-compacting concrete, which is made of the following components in parts by mass: 243 parts of cement, 233 parts of fly ash, 1112 parts of sand, 515 parts of sintered stone, 210 parts of water, 6 parts of admixture, and 5 parts of sodium silicate.
[0033] The admixture is a mixture of HSNG-T water reducer and YQ-AE air entraining agent, and the mass ratio of HSNG-T admixture to YQ-AE air entraining agent is 10:1.
[0034] When using sodium silicate, it needs to be configured into a sodium silicate solution with a mass fraction of 15%.
[0035] The water-cement ratio is 0.85 and the water temperature is 60°C.
[0036] This embodiment provides a method for preparing sintered stone self-compacting concrete, comprising the following steps: (1) According to the construction mix ratio of concrete raw materials, 243 parts of cement and 233 parts of fly ash were weighed, added into a mixer and stirred thoroughly to obtain a powder material.
[0037] (2) Weigh 1112 parts of sand and 515 parts of sintered stone according to the raw material ratio, add them to the powder material that has just been mixed, and continue to stir. The dry mixing time is about 90 seconds to fully mix the powder material and aggregate to ensure that there is no obvious unevenness. (3) After dry mixing is completed, 6 parts of admixture and 210 parts of water are slowly poured into the mixer while it is working. Stirring is continued for 150 seconds until the speed reaches 150 r / min. Finally, a sodium silicate solution with a mass fraction of 15% is added to obtain a mixture.
[0038] (4) Fill the mold with the mixed mixture, use its own high fluidity to fill the mold, and apply a plastering treatment to the surface. Curing for 28 days will obtain sintered stone self-compacting concrete.
[0039] Example 2 The present embodiment provides a sintered stone self-compacting concrete, which is made of the following components in parts by mass: 243 parts of cement, 233 parts of fly ash, 1069 parts of sand, 596 parts of sintered stone, 206 parts of water, 7 parts of admixture, and 5 parts of sodium silicate.
[0040] The admixture is a mixture of HSNG-T water reducer and YQ-AE air entraining agent, and the mass ratio of HSNG-T admixture to YQ-AE air entraining agent is 10:1.
[0041] When using sodium silicate, it needs to be configured into a sodium silicate solution with a mass fraction of 15%.
[0042] The water-cement ratio is 0.85 and the water temperature is 60°C.
[0043] This embodiment provides a method for preparing sintered stone self-compacting concrete, comprising the following steps: (1) According to the construction mix ratio of concrete raw materials, 243 parts of cement and 233 parts of fly ash were weighed, added into a mixer and stirred thoroughly to obtain a powder material.
[0044] (2) According to the raw material ratio, weigh 1069 parts of sand and 596 parts of sintered stone, add them to the powder material that has just been mixed, and continue stirring. The dry mixing time is about 90 seconds to ensure that the powder material and aggregate are fully mixed to ensure that there is no obvious unevenness.
[0045] (3) After dry mixing is completed, 7 parts of admixture and 206 parts of water are slowly poured into the mixer while it is working, and stirring is continued for 150 seconds until the speed reaches 150 r / min. Finally, sodium silicate solution is added to obtain a mixture.
[0046] (4) Fill the mold with the mixed mixture, use its own high fluidity to fill the mold, and apply a plastering treatment to the surface. Curing for 28 days will obtain sintered stone self-compacting concrete.
[0047] Example 3 The present embodiment provides a sintered stone self-compacting concrete, which is made of the following components in parts by weight: 243 parts of cement, 233 parts of fly ash, 1055 parts of sand, 623 parts of sintered stone, 204 parts of water, 8 parts of admixture, and 5 parts of sodium silicate.
[0048] The admixture is a mixture of HSNG-T water reducer and YQ-AE air entraining agent, and the mass ratio of HSNG-T admixture to YQ-AE air entraining agent is 10:1.
[0049] When using sodium silicate, it needs to be configured into a sodium silicate solution with a mass fraction of 15%.
[0050] The water-cement ratio is 0.85 and the water temperature is 60°C.
[0051] This embodiment provides a method for preparing sintered stone self-compacting concrete, comprising the following steps: (1) According to the construction mix ratio of concrete raw materials, 243 parts of cement and 233 parts of fly ash were weighed, added into a mixer and stirred thoroughly to obtain a powder material.
[0052] (2) According to the raw material ratio, weigh 1055 parts of sand and 623 parts of sintered stone, add them to the powder material that has just been mixed, and continue stirring. The dry mixing time is about 90 seconds to ensure that the powder material and aggregate are fully mixed to ensure that there is no obvious unevenness.
[0053] (3) After dry mixing is completed, 8 parts of admixture and 204 parts of water are slowly poured into the mixer while it is in operation. Stirring is continued for 150 seconds until the speed reaches 150 r / min. Finally, sodium silicate solution is added to obtain a mixture.
[0054] (4) Fill the mold with the mixed mixture, use its own high fluidity to fill the mold, and apply a plastering treatment to the surface. Curing for 28 days will obtain sintered stone self-compacting concrete.
[0055] Comparative Example 1 This comparative example provides a self-compacting concrete, which is made of the following components in parts by mass: 243 parts of cement, 233 parts of fly ash, 1069 parts of sand, 596 parts of natural crushed stone, 206 parts of water, and 7 parts of admixture.
[0056] The admixture is a mixture of HSNG-T water reducer and YQ-AE air entraining agent, and the mass ratio of HSNG-T admixture to YQ-AE air entraining agent is 10:1.
[0057] The water-cement ratio is 0.85 and the water temperature is 60°C.
[0058] This comparative example provides a method for preparing a self-compacting concrete, comprising the following steps: (1) According to the construction mix ratio of concrete raw materials, 243 parts of cement and 233 parts of fly ash were weighed, added into a mixer and stirred thoroughly to obtain a powder material.
[0059] (2) Weigh 1069 parts of sand and 596 parts of natural gravel according to the raw material ratio, add them to the powder material that has just been mixed, and continue stirring. The dry mixing time is about 90 seconds to ensure that the powder material and aggregate are fully mixed to ensure that there is no obvious unevenness.
[0060] (3) After dry mixing is completed, 7 parts of admixture and 206 parts of water are slowly poured into the mixer while it is in operation. Stirring is continued for 150 seconds until the speed reaches 150 r / min to obtain a mixture.
[0061] (4) Fill the mold with the mixed mixture, use its own high fluidity to fill the mold, and apply a plastering treatment to the surface. Curing for 28 days will obtain self-compacting concrete.
[0062] The performance of the self-compacting concrete prepared in the examples and comparative examples was tested below.
[0063] Expansion and slump test: Use a slump cone to measure. Lift it vertically after filling it. The self-compacting concrete flows under the action of gravity. The expansion is considered qualified when it is between 650mm~750mm, and the slump is considered qualified when it is between 260mm~270mm.
[0064] V-funnel: After the self-compacting concrete fills the V-funnel, it falls freely. It is considered qualified when the time it takes to completely pass through is between 7s and 25s.
[0065] Gas content: Measured using a gas cylinder.
[0066] Compressive strength: Tested using a microcomputer-controlled electronic universal testing machine.
[0067] The performance test results of the sintered stone self-compacting concrete prepared in Examples 1 to 3 and the self-compacting concrete prepared in Comparative Example 1 are shown in Table 2.
[0068] Table 2 Properties of sintered stone self-compacting concrete prepared with different mix ratios Compared with comparative example 1, the strength of example 2 is increased by 20%. This is because the porous structure of the sintered stone increases the specific surface area with the cementitious material, resulting in better bonding performance and improved strength.
[0069] In Example 1-Example 3, after the proportion of sintered stone in the total mass of cement and fly ash is increased, the high-temperature stability is improved. This is because when the self-compacting concrete encounters high temperature, the sintered stone can exist as a stable skeleton structure to inhibit the internal volume expansion caused by high temperature.
[0070] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0071] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A sintered stone self-compacting concrete, characterized in that: It is made of the following components in parts by mass: 243 parts of cement, 233 parts of fly ash, 1055 parts to 1112 parts of sand, 515 parts to 623 parts of sintered stone, 204 parts to 210 parts of water, 6 parts to 8 parts of admixture, and 5 parts of sodium silicate.
2. The sintered stone self-compacting concrete according to claim 1, characterized in that: The particle size of sintered stone is 5mm~30mm, and the bulk density is 800kg / m 3 ~1200kg / m 3 .
3. The sintered stone self-compacting concrete according to claim 1, characterized in that: The admixtures are water reducer and air entraining agent, and the mass ratio of water reducer to air entraining agent is 10:
1.
4. The sintered stone self-compacting concrete according to claim 1, characterized in that: The cement is ordinary Portland cement.
5. The sintered stone self-compacting concrete according to claim 1, characterized in that: The fly ash is Grade I fly ash.
6. A method for preparing sintered stone self-compacting concrete according to any one of claims 1 to 5, characterized in that: The following steps are involved: After cement and fly ash are mixed evenly, sand and sintered stone are added and mixed evenly, and then admixtures, water and sodium silicate solution are added and mixed evenly and then cured to obtain sintered stone self-compacting concrete.
7. The method for preparing sintered stone self-compacting concrete according to claim 6, characterized in that: The curing time is 28 days.
8. The method for preparing sintered stone self-compacting concrete according to claim 6, characterized in that: The mass fraction of sodium silicate solution is 15%.
9. Use of the sintered stone self-compacting concrete according to any one of claims 1 to 5 in dam engineering and lining engineering.
Citation Information
Patent Citations
Method for manufacturing concrete from reclaimed coal slag and ash
CN106477928A
Intersected concrete of fly ash-based geopolymeric concrete and ordinary concrete and preparation process of intersected concrete
CN110183165A
Calcined stone alkali-activated light high-strength concrete as well as preparation and construction methods thereof
CN116161916A
Environment-friendly solid waste recycled concrete and preparation method thereof
CN118930153A
Raw material mixture for production of heat-resistant fibre-vermiculite-pumice concrete
RU2811049C1